Analisis Sejarah Masuk dan Berkembangnya Islam di Kawasan Asia Tenggara - Intan Tria Rahayu; Moly Santya; Meilin Faiza Pramuswari; Rizky Oktariyani; Maryamah Maryamah (Departement of Mathematics Education, 2023)
This research is entitled Analysis of the history of the entry and development of Islam in the Southeast Asia region. The research aims to describe and analyze the process of the entry and development of Islam in the Southeast Asia region. Islam began to enter Southeast Asia in 7 AD through trade from Arabs. It should be noted that Malay civilization also appeared in Indonesia in 300-200 BC via the eastern route, which ultimately spread to various regions of Indonesia. The data in this research are in the form of words and sentences taken from several educational articles by analyzing the results. The data in this research was collected through 3 stages, namely first, data reduction such as selecting, summarizing and classifying. Second, presenting data with classifications focused on research and third, making conclusions based on data that has been collected based on research. As time goes by, Islam increasingly develops and spreads widely in various regions of Indonesia such as Sumatra, West Java, East Java and other areas.